Components of anti-crisis potential of construction enterprises in dynamic conditions - Skupsky, R. (Ways to Improve Construction Efficiency, 2018)
The concept of "anti-crisis potential" of a construction company is defined. The structure of anti-crisis potential of a construction enterprise is investigated. The main problems of functioning of enterprises of the construction industry of Ukraine in the pre-crisis period and in the newest political and economic conditions of the country's integration into the EU are identified. The latest trends in the development of construction in terms of full or partial integration with EU markets are substantiated.